EXPLORING SECONDARY STUDENTS’ PERCEPTIONS TOWARDS LEARNING ENGLISH THROUGH MOVIES - Mutiara Ayu; Dion Tira Erlangga (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2022)
The use of media can encourage students to learn English more interestingly. Students are less motivated to learn English in the classroom by using textbooks, but they are more interested in learning English by watching English movies. The purpose of this study was to investigate students' perceptions of learning English through movies as well as students' obstacles to learning English through movies. A case study was used to conduct this research. It was carried out in one class of eleventh grade students of a private senior high school in Bandar Lampung. The information was gathered through questionnaire and interview. The data were analysed by data collection, data disassemble, data reassemble, data interpreting and conclusion. Based on the findings, students have positive attitudes toward learning English through movies. Students benefited from watching English movies in a variety of ways, including improving their pronunciation skills, learning the proper way to pronounce English words, and increasing their vocabulary mastery. Students can benefit from watching English movies to become acquainted with basic conversation and expressions that they can use to begin conversing in their daily lives. Meanwhile, students face some challenges when learning English through movies, such as feeling difficult when the speakers speak very quickly and feeling complicated when they find uncommon words in the movies.